Cornual heterotopic pregnancy after in vitro fertilization: management by laparoscopic repair - Dokuzeylül Güngör, Nur; Gürbüz, Tuğba (The European Research Journal, 2019)
The incidence of heterotopic pregnancy has risen dramatically with the widespread use of assisted reproductive technology. The risk factors for this pathology include tubal infertility, cleavage stage embryo transfer and frozen embryo transfer. Herein we report two cases with cornual heterotopic pregnancy after in vitro fertilization/embryo transfer. They managed by laparoscopic cornual repair or salpingectomy. Early diagnosis and appropriate management of heterotopic pregnancy may lead to a favorable prognosis.